Методика енергетичних розрахунків можливості радіопридушення - Федішин, Є. А. (ХНУРЕ, 2024)
A brief overview of the fundamentals of the theory of radio electronic suppression of radio communication lines has been conducted. In particular, the influence of active intentional radio interference on the functioning of radio communication means has been determined. This includes classification and brief characterization of organized radio interference. The peculiarities of suppression of UHF radio communication lines are considered. A methodology for searching for effective radio interference structures has been developed, as well as a methodology for synthesizing optimal radio interference. Energy calculations of the possibility of radio suppression of ground UHF radio communication lines have been carried out.
Keywords: радіопридушення